LITOSTRATIGRAFI CEKUNGAN OMBILIN DALAM KERANGKA TECTONO-SEDIMENTATION RIFT BASIN - Mulyana, Budi; Gani, Reza Mochamad Ganjar (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
During Tertiary, the sedimentation model in Ombilin Basin, West Sumatra, was strongly influenced by tectonisme. It is indicated by characteristic and composition of the rock, and distribution pattern for each formation. In general, it can be decided into two main groups according to the age of rocks, which associated with the tectono-sedimentation rift basin. Brani, Sangkarewang, Sawahlunto and Sawahtambang Formations were deposited in terrestrial to transition zone during syn-rift phase. Meanwhile, Ombilin and Ranau Formations, which is dominated by volcanic deposits, were formed for the period of post-rift phase indicated by marine influence has existed.